Prisoner of night and fog - Blankman, Anne (Balzer + Bray, an imprint of HarperCollinsPublishers, 2015)
In 1930s Munich, the favorite niece of rising political leader Adolph Hitler is torn between duty and love after meeting a fearless and handsome young Jewish reporter.